An Experimental Approach to CDMA and Interference Mitigation From System Architecture to Hardware Testing through VLSI Design - Fanucci, Luca. (Springer US, 2004)
An Experimental Approach to CDMA and Interference Mitigation was written with the admittedly ambitious intent of filling the gap between communication theory and VLSI implementation, and thus to provide a more general/theoretical approach to the design, development, and testing of a CDMA receiver. As a consequence, the concepts and techniques that are presented turn out to be applicable to a more general kind of digital wireless modems in terms of receiver architecture design and implementation. As the reader will easily find out, the subject of digital modem design and implementation is addressed in the book starting from a theoretical approach (supported by proper bibliographic references), and is followed by application issues, with reference to an ESA experiment assumed as a case study. A complete design flow, from specification to implementation, including testing and final verification is then presented. This leads the reader step-by-step to a thorough understanding of CDMA transmission and detection, and constitutes a practical guidance for the design of VLSI wireless mobile terminals.